Efficacy of Melatonin in Animal Models of Subarachnoid Hemorrhage: A Systematic Review and Stratified Meta-Analysis - Hu, Xiangyu; Zhu, Yuwei; Zhou, Fangfang; Peng, Cuiying; Hu, Zhiping; Chen, Chunli (Frontiers in Neurology, 2021)
Background and Purpose: Subarachnoid hemorrhage (SAH) is a severe disease which is characterized by sudden headaches, loss of consciousness or focal neurological deficits. Melatonin (MEL) has been reported as a potential neuroprotective agent of SAH. It provides protective effects through the anti-inflammatory effects or the autophagy pathway. Our systematic review aims to evaluate the efficacy of MEL administration on experimental SAH animals and offer support for the future clinical trial design of the MEL treatment following SAH. Methods: The following online databases were searched for experimentally controlled studies of the effect of MEL on SAH models: PubMed, Web of Knowledge, Embase and China National Knowledge Infrastructure (all until March 2021). The MEL effect on the brain water content (BWC) and neurological score (NS) were compared between the treatment and control groups using the standardized mean difference (SMD). Results: Our literature identified 160 possible articles, most of them were excluded due to duplication (n = 69) and failure to meet the inclusion criteria (n = 56). After screening the remaining 35 articles in detail, we excluded half of them because of no relevant outcome measures (n = 16), no relevant interventions (n = 3), review articles (n=1), duplicated publications (n = 1) and studies on humans or cells (n = 2). Finally, this systematic review contained 12 studies between 2008 to 2018. All studies were written in English except for one study in Chinese, and all of them showed the effect of melatonin on BWC and NS in SAH models. Conclusion: Our research shows that melatonin can significantly improve the behavior and pathological results of SAH animal models. However, due to the small number of studies included in this meta-analysis, the experimental design and experimental method limitations should be considered when interpreting the results. Significant clinical and animal studies are still required to evaluate whether melatonin can be used in the adjuvant treatment of clinical SAH patients.